A dialogue with the texts of Floriy Batsevych - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2024)
The author’s concept of the Ukrainian linguist Florii Batsevych is considered in the article in the categories of communicative studies. The scientific output of the scientist is large and presented in various aspects. It is possible to observe certain chronological cycles of serious publications in which related or analogous linguistic phenomena are analyzed in detail and in a harmonious correction of the theory and real life of the word. Linguist texts of different genres and subject matter, built on communicative principles – monographs, textbooks, with an appeal to small formats of scientific writing, such as, in particular, an article – are analyzed. It is claimed that the common features of the author’s conceptual consideration of texts are based on the internal logic of philological proofs, the systematicity of analysis, the sequence of statements, clearly formulated partial and general conclusions, the principle of proofs from simple to complex in the model from general statements to specific issues of communicative studies. Emphasis is also placed on the consistency and clearness of the definitions in F. Batsevych’s operational terminology. The article emphasizes the importance and correctness of F. Bacevych’s analysis of language facts in the broad context of the cultural and social reality of Ukraine, which, accordingly, allows us to appeal to the possibilities and results of other branches of science – linguistic psychology, linguistic philosophy, literary studies, etc. Attention is also drawn to the encyclopedic nature of F. Batsevych’s knowledge, the skill and correctness of the author’s vocations, reminiscences, intertextual echoes with the texts of Ukrainian and European researchers. In the interpretation of F. Batsevych, the strange texts studied for the first time in Ukrainian linguistics are logically explainable and demonstrable as an opportunity to understand the subconscious expressed in special forms or specially constructed variants of its linguistic expression.